MANAJEMEN BERBASIS MUTU - Ella Siti Chaeriah (Jurnal Manajemen Bisnis Krisnadwipayana, 2016)
Quality management is a phenomenon. Advanced culture that supports arts and crafts allow shoppers choose goods with higher quality standards compared to the normal stuff. In a society that appreciates the arts and crafts, one of the tasks of the management company or owner of the company is the head of the workshop, as well as train and supervise employees and interns. The company set the standard, assessing the work of the employees and ordered rework or repair is necessary. Jobs in crafts has a limitation that is only capable of producing little other dipihak products, but has the advantage that is every product can be made independently in accordance with the wishes of the customer. Craft work approach towards quality score is the primary input when the initial establishment of quality management as a part of management science.